Are the G20 economies making enough progress to meet their NDC targets?. (March 2019) - den Elzen, Michel; Kuramochi, Takeshi; Höhne, Niklas; Cantzler, Jasmin; Esmeijer, Kendall; Fekete, Hanna; Fransen, Taryn; Keramidas, Kimon; Roelfsema, Mark; Sha, Fu; van Soest, Heleen; Vandyck, Toon
Abstract: Under the Paris Agreement, countries committed to a variety of climate actions, including post-2020 greenhouse gas (GHG) emissions reduction targets. This study compares projected GHG emissions in the G20 economies under current climate policies to those under the GHG targets outlined in the nationally determined contributions (NDCs). It is based on an assessment of official governmental estimates and independent national and global studies. The study concludes that six G20 members (China, India, Indonesia, Japan, Russia and Turkey) are projected to meet their unconditional NDC targets with current policies. Eight members (Argentina, Australia, Canada, the European Union, Republic of Korea, South Africa and the United States) require further action to achieve their targets. Insufficient information is available for Saudi Arabia, and emission projections for Brazil and Mexico are subject to considerable uncertainty. The study also presents high-level decarbonisation indicators to better understand the current progress towards meeting the NDCs – Saudi Arabia and South Africa were found to continue increasing both emission intensity per unit GDP and emissions per capita under current policies by 2030 from 2015 levels. Highlights: Almost all G20 members are making progress in implementing climate policies. Eight G20 members are on track to meet their unconditional NDC targets. The other G20 members require enhanced policies to achieve their NDC targets. For many G20 members emissions continue to increase through 2030. High-level decarbonisation indicators to enhance understanding of the mitigation are presented.